MECHANISMS FOR ATTRACTING ECONOMIC RESOURCES BY SMALL BUSINESSES AND PRIVATE ENTREPRENEURSHIP - Mirzakholikov Bobir Bakhtierovich (Scholar Express Journals, 2021)
The article considers the importance of the development of small business and private entrepreneurship in the development of the national economy, its organizational forms. Special emphasis is placed on the consideration of newly formed mechanisms for attracting financial sources for the further development of the activities of small businesses and private entrepreneurship. The article considers the controversy of foreign scientists about the essence and importance of public-private partnership in attracting financial sources for the further socio - economic development of the region
Keywords: Private entrepreneurship; small business; creation; supply